2017
DOI: 10.20517/2574-1209.2016.10
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 as a potential biomarker of metabolic disorders and cardiovascular remodeling in patients with hypertension and type 2 diabetes

Abstract: How to cite this article: Bobronnikova L. Galectin-3 as a potential biomarker of metabolic disorders and cardiovascular remodeling in patients with hypertension and type 2 diabetes. Vessel Plus 2017;1:61-7. Aim:To determine the impact of galectin-3 levels on the progression of metabolic disorders and structural-functional changes in the myocardium and blood vessels in patients with concomitant systemic arterial hypertension (AH) and type 2 diabetes mellitus (type 2 DM). Methods: Ninety-five patients with hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Furthermore, cardiac inflammation and lipotoxicity in obese patients has been attributed to Gal-3 pro-inflammatory properties [ 189 ]. Some studies have even suggested Gal-3 as a potential biomarker of metabolic dysregulation and cardiovascular remodelling in patients with hypertension and T2DM [ 190 ]. Intriguingly, some beneficial effects of Gal-3 have been described.…”
Section: Galectins In Metabolic Disordersmentioning
confidence: 99%
“…Furthermore, cardiac inflammation and lipotoxicity in obese patients has been attributed to Gal-3 pro-inflammatory properties [ 189 ]. Some studies have even suggested Gal-3 as a potential biomarker of metabolic dysregulation and cardiovascular remodelling in patients with hypertension and T2DM [ 190 ]. Intriguingly, some beneficial effects of Gal-3 have been described.…”
Section: Galectins In Metabolic Disordersmentioning
confidence: 99%
“…Estudios clínicos han demostrado que los niveles de Gal-3 en sujetos con HA y DM2 fueron mayores que en el grupo control (p<0,05), esto posiblemente asociado a estrés cardiaco, niveles elevados de angiotensina II (Ang II) y sobrecarga de las cámaras cardiacas por presión elevada (6). Se sugiere que la secreción de Gal-3 está mediada por macrófagos, quienes representan un factor importante en la acumulación y activación de miofibroblastos, siendo estos últimos capaces de inducir fibrosis cardiaca.…”
Section: Participación De Galectina-3 Y Tgf-β1unclassified
“…Galectin-3 ( Gal-3 ) is a member of the -galactoside-binding family of proteins [5] . It is produced by numerous cells, including vascular, epithelial, interstitial, and immune cells.…”
Section: Introductionmentioning
confidence: 99%